That elusive elasticity : a long-panel approach to estimating the capital-labor substitution elasticity - Robert S. Chirinko; Steven M. Fazzari; Andrew P. Meyer (Center for Economic Studies and ifo Institute (CESifo), 2004)
The elasticity of substitution between capital and labor features prominently in several areas of economic research. However, a consensus estimate remains elusive. We develop an estimation strategy that filters panel data in an original way and avoids several pitfalls - difficult-to-specify dynamics, transitory time-series variation, and positively sloped supply schedules - inherent in investment equations that can bias the estimated elasticity. Results are based on an extensive panel containing 1,860 manufacturing and non-manufacturing firms. Our model generates a precisely estimated elasticity of approximately 0.40. The method developed here may prove useful in estimating other structural parameters from panel datasets.
Keywords: E22; H32; 330; Kapital; Arbeit; Faktorsubstitution; Substitutionselastizität; Panel; Schätzung; Vereinigte Staaten